Unprecedented 34S‐enrichment of pyrite formed following microbial sulfate reduction in fractured crystalline rocks. Issue 5 (27th June 2018) - Drake, Henrik; Whitehouse, Martin J.; Heim, Christine; Reiners, Peter W.; Tillberg, Mikael; Hogmalm, K. Johan; Dopson, Mark; Broman, Curt; Åström, Mats E.
Abstract: In the deep biosphere, microbial sulfate reduction (MSR) is exploited for energy. Here, we show that, in fractured continental crystalline bedrock in three areas in Sweden, this process produced sulfide that reacted with iron to form pyrite extremely enriched in 34 S relative to 32 S. As documented by secondary ion mass spectrometry (SIMS) microanalyses, the δ 34 Spyrite values are up to +132‰V‐CDT and with a total range of 186‰. The lightest δ 34 Spyrite values (−54‰) suggest very large fractionation during MSR from an initial sulfate with δ 34 S values (δ 34 Ssulfate, 0 ) of +14 to +28‰. Fractionation of this magnitude requires a slow MSR rate, a feature we attribute to nutrient and electron donor shortage as well as initial sulfate abundance. The superheavy δ 34 Spyrite values were produced by Rayleigh fractionation effects in a diminishing sulfate pool. Large volumes of pyrite with superheavy values (+120 ± 15‰) within single fracture intercepts in the boreholes, associated heavy average values up to +75‰ and heavy minimum δ 34 Spyrite values, suggest isolation of significant amounts of isotopically light sulfide in other parts of the fracture system. Large fracture‐specific δ 34 Spyrite variability and overall average δ 34 Spyrite values (+11 to +16‰) lower than the anticipated δ 34 Ssulfate, 0 support this hypothesis. The superheavy pyrite found locally in the borehole intercepts thus represents a late stage in a much larger fracture system undergoing Rayleigh fractionation. Microscale Rb–Sr dating and U/Th–He dating of cogenetic minerals reveal that most pyrite formed in the early Paleozoic era, but crystal overgrowths may be significantly younger. The δ 13 C values in cogenetic calcite suggest that the superheavy δ 34 Spyrite values are related to organotrophic MSR, in contrast to findings from marine sediments where superheavy pyrite has been proposed to be linked to anaerobic oxidation of methane. The findings provide new insights into MSR‐related S‐isotope systematics, particularly regarding formation of large fractions of 34 S‐rich pyrite.